Gaultheria gonggashanensis sp. nov. (Ericaceae) from Sichuan, China. (14th July 2015) - Fritsch, Peter W.; Lu, Lu; Wang, Hong
<x xml:space="preserve">Abstract</x> Gaultheria gonggashanensis P. W. Fritsch & Lu Lu, a new species from western Sichuan Province, China, is described and illustrated. This species belongs to Gaultheria ser. Trichophyllae Airy Shaw and is most similar to G. sinensis J. Anthony, but differs by its longer stem setae, glabrous petioles and leaf blade midveins adaxially, thick‐chartaceous to subcoriaceous leaf blades, larger calyx lobes, and smaller anther thecae. The species is known with certainty only from the Hailuo Valley on the east slope of Mount Gongga in the Daxue Range.